Boron neutron capture therapy in the context of tumor heterogeneity: progress, challenges, and future perspectives - Zhou, Rongmiao; You, Zhun; Liu, Liang (Frontiers in Oncology, 2025)
Boron neutron capture therapy (BNCT), as an emerging binary treatment method, has shown the advantage of effectively treating tumors while sparing normal tissues, utilizing the characteristics of boron’s nuclear capture and fission reactions, as well as the distinct distribution of boron delivery agents in tumor tissues and healthy tissues. Currently, numerous boron delivery agents have been developed to improve their targeting property, biocompatibility, solubility, and nuclear localization capability. The shift of neutron source from being based on nuclear reactors to being based on accelerators facilitates the conduct of clinical trials. BNCT has demonstrated promising results in treating head and neck cancers, gliomas, and skin melanomas. In addition, researches on the application of BNCT have been carried out in other tumors, such as liver cancer, lung cancer, and breast cancer. Notably, in 2020, BNCT was approved for clinical use in the treatment of unresectable locally advanced or locally recurrent head and neck cancer. Subsequently, post-marketing surveillance confirmed its safety and efficacy. Despite the progress made, BNCT still encounters substantial challenges in enhancing its efficacy. This review provides a comprehensive synthesis of the literature on BNCT over the last decade. It systematically examines the treatment’s mechanism of action, the landscape of clinical research, key markers and factors influencing therapeutic efficacy, and the primary challenges and future directions for the field. The development of BNCT is impeded by several significant challenges, including the research and development of boron delivery agents, the construction of neutron sources, the management of tumor heterogeneity, the advancement of clinical translation, and the securement of economic and logistical support. These challenges can only be systematically overcome through the organic integration of technological innovation, policy support, clinical standardization, and cross-disciplinary collaboration, thereby creating a synergistic effect.